Non-destructive methods to assess pesticide exposure in free-living bats - Natalia Sandoval-Herrera; Jesusa Paz Castillo; Ma. Enrica Angela Ching; L. Gerardo Herrera M.; Paul A. Faure; Kenneth Welch (Science of The Total Environment, 2023)

Comparative genomics and physiology of the genus Methanohalophilus , a prevalent methanogen in hydraulically fractured shale - Mikayla A. Borton; Rebecca A. Daly; Bridget O'Banion; David W. Hoyt; Daniel N. Marcus; Susan Welch; Sybille S. Hastings; Tea Meulia; Richard A. Wolfe; Anne E. Booker; Shikha Sharma; David R. Cole; et al. (Environmental Microbiology, 2018)
Summary About 60% of natural gas production in the United States comes from hydraulic fracturing of unconventional reservoirs, such as shales or organic‐rich micrites. This process inoculates and enriches for halotolerant microorganisms in these reservoirs over time, resulting in a saline ecosystem that includes methane producing archaea. Here, we survey the biogeography of methanogens across unconventional reservoirs, and report that members of genus Methanohalophilus are recovered from every hydraulically fractured unconventional reservoir sampled by metagenomics. We provide the first genomic sequencing of three isolate genomes, as well as two metagenome assembled genomes (MAGs). Utilizing six other previously sequenced isolate genomes and MAGs, we perform comparative analysis of the 11 genomes representing this genus. This genomic investigation revealed distinctions between surface and subsurface derived genomes that are consistent with constraints encountered in each environment. Genotypic differences were also uncovered between isolate genomes recovered from the same well, suggesting niche partitioning among closely related strains. These genomic substrate utilization predictions were then confirmed by physiological investigation. Fine‐scale microdiversity was observed in CRISPR‐Cas systems of Methanohalophilus , with genomes from geographically distinct unconventional reservoirs sharing spacers targeting the same viral population. These findings have implications for augmentation strategies resulting in enhanced biogenic methane production in hydraulically fractured unconventional reservoirs.

Wingbeat kinematics and energetics during weightlifting in hovering hummingbirds across an elevational gradient - Derrick J. E. Groom; M. Cecilia B. Toledo; Kenneth C. Welch (Journal of Comparative Physiology B, 2017)

13C-Breath testing in animals: theory, applications, and future directions - Marshall D. McCue; Kenneth C. Welch (Journal of Comparative Physiology B, 2016)

Sugar flux through the flight muscles of hovering vertebrate nectarivores: a review - Kenneth C. Welch; Chris C. W. Chen (Journal of Comparative Physiology B, 2014)